2014
DOI: 10.1111/sdi.12194
|View full text |Cite
|
Sign up to set email alerts
|

Laughter and Humor Therapy in Dialysis

Abstract: Laughter and humor therapy have been used in health care to achieve physiological and psychological health-related benefits. The application of these therapies to the dialysis context remains unclear. This paper reviews the evidence related to laughter and humor therapy as a medical therapy relevant to the dialysis patient population. Studies from other groups such as children, the elderly, and persons with mental health, cancer, and other chronic conditions are included to inform potential applications of lau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(49 citation statements)
references
References 44 publications
0
43
0
5
Order By: Relevance
“…Śmiech i dobry nastrój mają korzystny wpływ na zmniejszenie nasilenia objawów zaburzeń nastroju [5] oraz psychotycznych [6], wspomagają również proces leczenia chorób somatycznych, redukując smutek i lęk, a także zmniejszając ból, poprawiając wydolność oddechową i jakość snu oraz zwiększając biologiczną odporność organizmu [7]. Pozytywne nastawienie związane jest…”
Section: Wstępunclassified
“…Śmiech i dobry nastrój mają korzystny wpływ na zmniejszenie nasilenia objawów zaburzeń nastroju [5] oraz psychotycznych [6], wspomagają również proces leczenia chorób somatycznych, redukując smutek i lęk, a także zmniejszając ból, poprawiając wydolność oddechową i jakość snu oraz zwiększając biologiczną odporność organizmu [7]. Pozytywne nastawienie związane jest…”
Section: Wstępunclassified
“…[6,18] They also suggest that it is a valid and reliable scale to evaluate the effect of multidimensional humor, in people with terminal stage CKD. This scale can provide important contributions to nursing interventions (Humor) [8] related to sense of humor evaluation in patients with terminal stage CKD during hemodialysis session [5] and it can be applied to people with chronic disease.…”
Section: Implications For Nursing Educators and Practicementioning
confidence: 99%
“…In a study conducted in Norway, with 52 persons undergoing hemodialysis followed for two years, it was found that higher levels of sense of humor had a negative association with stressors and mortality related to the disease. [5] Humor is a construct that is closely related to well-being and is considered a complex phenomenon, clearly personal in nature. The standard sense of humor varies from person to person and changes according to the humor, the personality, the situation, the level of attention, the importance given to the situation, among other things.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2011 the European federation of hospital clowns was founded [6]. Previous reviews reported the effects of clown hospital on anxiety and pain but there was no comprehensive review of studies methodical design which assessed benefits of hospital clowning interventions [3,7,8]. The aim of this literature review is to analyze design of the studies, relating to the benefit of hospital clown interventions for hospitalized children.…”
Section: Introductionmentioning
confidence: 99%